2017
DOI: 10.1080/1828051x.2017.1283544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bamboo charcoal powder including vinegar supplementation on performance, eggshell quality, alterations of intestinal villi and intestinal pathogenic bacteria populations of aged laying hens

Abstract: This study examined the supplementation level effects of bamboo charcoal powder including vinegar (BCV) on performance, eggshell quality, alterations of intestinal villi and intestinal pathogenic bacteria populations, in aged laying hens. A total of 200 laying hens (60 weeks of age) were randomly allotted into four treatment groups, with five replicates per treatment and 10 hens per replicate. Hens were fed a basal diet, supplemented with BCV at 0, 0.5, 1.0 or 1.5% level, ad libitum for 12 weeks. Egg productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Organic acids, which account for the low pH of the sample, are produced by the thermal pyrolysis of xylans [21]. The present PA sample consisted of 7.5% of organic acids (mainly acetic, propionic, and formic acid), as compared with those previously reported by Rattanawut et al (2.8%) [22], Hou et al (3.10%) [23], and Oramahi et al (between 3.6 and 4.3%) [24]. Phenolics, such as catechol (5.6%) and methylcatechol (1.2%), were also observed in higher concentrations as compared with previous studies by Xu et al (4.62%) [25] and Fagernäs et al (0.16%) [26].…”
Section: Characterization Of Pasupporting
confidence: 59%
“…Organic acids, which account for the low pH of the sample, are produced by the thermal pyrolysis of xylans [21]. The present PA sample consisted of 7.5% of organic acids (mainly acetic, propionic, and formic acid), as compared with those previously reported by Rattanawut et al (2.8%) [22], Hou et al (3.10%) [23], and Oramahi et al (between 3.6 and 4.3%) [24]. Phenolics, such as catechol (5.6%) and methylcatechol (1.2%), were also observed in higher concentrations as compared with previous studies by Xu et al (4.62%) [25] and Fagernäs et al (0.16%) [26].…”
Section: Characterization Of Pasupporting
confidence: 59%
“…This was likely because bamboo charcoal absorbs excess nutrients in feed and improves the absorption and metabolic capacity of the digestive tract by slowing down the release of nutrients. However, dietary bamboo charcoal supplementation significantly reduces the average daily feed intake [ 28 ]. Additionally, carbon supplementation has also been reported to inhibit growth when exposure concentrations are too high [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BVC has been shown to be an effective immunopotentiator and growth-promoter in domestic animals such as pigs, ducks, and chickens (Wang et al, 2012;Rattanawut et al, 2017Rattanawut et al, , 2018, its potency in the practice of aquaculture remains largely unknown. Data obtained in this study demonstrated that 90-d dietary BVC supplementation at the doses of 1% and 2% can significantly improve the survival and growth performance of the large-scale loach, indicating BVC could be a promising functional additive for the aquaculture of fish species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to applications in construction and furniture making, huge amount of bamboo are also used to produce secondary products such as bamboo charcoal and bamboo vinegar. Bamboo charcoal is a kind of biochar has many useful physical and chemical properties, such as large pores, large surface area, and rich surface functional groups (Rattanawut et al, 2017). Bamboo charcoal characterized by these porous structure and high mineral contents (i.e., calcium, iron, and sodium) are not only exploited in the production of various daily products such as toothpaste and face cream, but are also widely used as legal food additive (Watarai and Tana, 2005;Zhao et al, 2008;Jia et al, 2015;Rattanawut et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation